(untitled) (Research, Society and Development, 2020)
The result of the advancement and democratization of digital information and communication technologies (TDIC) has made it possible to expand contemporary educational trends such as the use of virtual learning environments (AVA) and distance education (EAD). However, the implementation of this online education resource still faces major challenges, among them, that of engaging, involving and motivating students’ actions in the environment. In this sense, the purpose of this article is to reflect on the use of playfulness in virtual learning environments. The research showed that the Ludicity applied to virtual environments may enable the enrichment of learning situations, as long as it is well planned and implemented in a systematic way considering the context in which the student is inserted. Finally, it is believed that the strategy of using Ludicity in AVA can improve the efficiency of learning processes in distance education.